Analisis Model Instructional Games dalam Materi Karangan Narasi pada Pelajaran Bahasa Indonesia di SD - Nur Rizky Amalia (el-Ibtidaiy:Journal of Primary Education, 2022)
Reading is a very important activity, which functions to make a large collection of words that students have so that students' communication becomes better, besides that reading can also make students wider, but in fact what happens in the current situation is less interest. read by students in Indonesia, this can be seen from the results of research conducted by UNESCO. The purpose of this research is to be able to see the results of the existing theoretical analysis by presenting the instructional game model theory which is expected to make students' reading interest better.The method uses literature review. Data to support this journal paper is sourced from the literature on the problems studied. Various kinds of literature references, namely books, scientific journals, papers and scientific articles, come from the internet. Writing maximizes the mutual continuity of each other and is in accordance with the subject matter of the discussion. The data obtained were filtered and sorted with the discussion pkpk, then conducted an assessment of scientific papers based on designed data that were interconnected with one another. The data analysis method is descriptive argumentative.The results showed that the implementation of learning to read narrative essays using an instructional game model that uses multimedia lectora inspire is very helpful for students, which is supported by existing theories, the instructional game model can help teachers in making a computer-based learning process with game offerings so that participants students can accept what the teacher's goals with a pleasant taste. Keywords: Instructional Games Model, Reading, Narrative